Explore and Develop a Culturally Adopted Behavioral Psycho Educational Family Intervention for Caregivers of Schizophrenic Patients in Egyptian Context. - Wahid, Rasha; Rathinasamy, Eilean Victoria Lazarus (Jour Med Resh and Health Sci, 2022)
Abstract Background: Schizophrenia is a severe enduring psychotic illness that has a profound impact on the life of the sufferer and imposes a heavy burden on their families and the community. Family interventions (FIs) are the accepted model for addressing caregivers’ needs for support and information. However, there are considerable variations in their content and application. The National Institute for Clinical Excellence (NICE) has recommended that FIs should be adapted when they are delivered to non-Western populations. To date, there are few published studies, which examine FIs in the Egyptian context. Aim: To explore and develop a culturally adopted behavioral psycho educational family intervention for caregivers of schizophrenic patients in Egyptian context. Methodology: Development phase involved four stages: 1). Identifying the strategies used for the cultural adaptation of FIs in non-Western cultures 2). Identifying the key components of FIs tested in the studies included in the Cochrane systematic review 3). A SWOT analysis to identify the strengths, weakness, opportunities and threats for the potential components (4). A focus group study involving caregivers and health professionals to explore the acceptability and feasibility of delivering FI in the Egyptian context. Data synthesis determined the design of the proposed intervention according to the findings obtained from the previous stages. Results: Four components were identified as the most frequently used out of the systematic review. Deep structure was adopted for cultural adaption. SWOT analysis identified areas of uncertainty regarding acceptability of the components. Focus group members recommended modifications to the components of the intervention to ensure its acceptability and feasibility in the local setting. Data synthesis was conducted and the intervention was designed. Conclusion This study provides evidence of the potential efficiency and acceptability of a culturally sensitive FI for caregivers of people with schizophrenia in Egypt. However, more work needs to be done to overcome the practical challenges and test the feasibility of the intervention in more rigorous way. Also, the efficacy of the intervention needs more rigorous investigation in the context of a small scale RCT.